ChemInform Abstract: Polar Order and Frustrated Antiferromagnetism in Perovskite Pb2MnWO6 Single Crystals. Issue 21 (6th May 2016) - Mathieu, Roland; et al.,
Abstract: Single crystals of the multiferroic title compound are prepared from mixtures of PbO, Mn2 O3, and WO3 (corundum crucible, Ar flow, 900 °C, 1 h).